2023
DOI: 10.3390/su15053954
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Shear Strength Parameters of Round Gravel Soils in Plateau Alluvial-Lacustrine Deposits and Its Application

Abstract: The shear strength parameters of conglomerate soils are crucial to the stability analysis of foundation support when excavating and supporting ultra-deep foundation pits in the highland alluvial lacustrine layer. The difference in water content of conglomerate soils in different regions will directly affect the values of shear strength parameters. At the same time, more research on the shear strength of conglomerate soils under different water contents is required. In this study, a series of large-scale direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Kong al. [10] discussed the influence of different water contents on the shear strength characteristics of round gravel soil, and used the shear strength parameters of round gravel soil with different water contents to numerically simulate the excavation and support of super deep foundation pits.…”
Section: Introductionmentioning
confidence: 99%
“…Kong al. [10] discussed the influence of different water contents on the shear strength characteristics of round gravel soil, and used the shear strength parameters of round gravel soil with different water contents to numerically simulate the excavation and support of super deep foundation pits.…”
Section: Introductionmentioning
confidence: 99%
“…Ecemis and Karaman [19] and Monkul and Ozden [20] studied the effect of fine particle content on the mechanical properties of clayey sand and found that fine particle content has a significant impact on its compression performance and liquefaction resistance. Kong et al [21] conducted in-depth research on the shear strength of conglomerate soil under different water contents. A large-scale direct shear test was conducted on circular gravel soil in the plateau alluvial-lacustrine deposit, and the shear strength curves and water content curves of the circular gravel soil under natural and saturated conditions were obtained, providing a certain reference for optimizing engineering design parameters.…”
Section: Introductionmentioning
confidence: 99%